2023
DOI: 10.1037/sgd0000574
|View full text |Cite
|
Sign up to set email alerts
|

Minority stress, pandemic stress, and mental health among gender diverse young adults: Gender dysphoria and emotion dysregulation as mediators.

Abstract: Gender diverse people in the United States are uniquely vulnerable to deleterious health outcomes because of long-enshrined systems of oppression and marginalization in American society. Trans young adults are especially vulnerable to these deleterious outcomes owing to their unique position in the life course. However, more research is needed on the mechanisms through which this marginalization contributes to mental health disparities in trans populations. Using a minority stress framework and online cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Based in Black feminist thought, intersectionality is a framework to interrogate social structures, power, and how systemic oppression differentially harms communities when considering the totalities of their identities and the histories and policies that position them within society (Crenshaw, 1991). A growing body of literature has examined the unique experiences of trans people of color (Galupo & Orphanidys, 2022; Minero et al, 2022) and how these individuals’ experiences differ from white trans individuals and cisgender people of color (Le et al, 2022; Pease et al, 2023). As a result of intersectional oppression, trans people of color experience rates of interpersonal and structural violence that are even higher than those faced by white trans people (Hennekam & Dumazert, 2023; Minero et al, 2022; Ussher et al, 2022), highlighting the need for intersectional work amid the largely white extant trans literature.…”
Section: Intersectionality and The Experiences Of Trans People Of Colormentioning
confidence: 99%
“…Based in Black feminist thought, intersectionality is a framework to interrogate social structures, power, and how systemic oppression differentially harms communities when considering the totalities of their identities and the histories and policies that position them within society (Crenshaw, 1991). A growing body of literature has examined the unique experiences of trans people of color (Galupo & Orphanidys, 2022; Minero et al, 2022) and how these individuals’ experiences differ from white trans individuals and cisgender people of color (Le et al, 2022; Pease et al, 2023). As a result of intersectional oppression, trans people of color experience rates of interpersonal and structural violence that are even higher than those faced by white trans people (Hennekam & Dumazert, 2023; Minero et al, 2022; Ussher et al, 2022), highlighting the need for intersectional work amid the largely white extant trans literature.…”
Section: Intersectionality and The Experiences Of Trans People Of Colormentioning
confidence: 99%
“…The identified dual burden of trans and non-binary specific health and service access challenges, together with pandemic-related health challenges, suggests that a psychological mediation framework may be applicable to examine the reasons trans and non-binary youth experienced the challenges discussed in the present study [16,35]. Specifically, based on a psychological mediation framework, losses of connection to gender-diverse communities may be mediating the impact of the dual burden of experiences with respect to access to healthcare [35].…”
Section: Plos Onementioning
confidence: 99%
“…Prior literature has suggested that the minority stress model may be applied to trans and non-binary populations to examine the unique stressors they may face (e.g., harassment, healthcare, and employment discrimination) during the pandemic, as well as the adverse health impacts from these stressors [13]. Additionally, as examined by Pease et al, a psychological mediation framework may supplement this conceptualization in gender diverse young adults, where gender dysphoria and emotion dysregulation may be modelled as mediators [16]. In comparison, Diamond and Alley suggest that insufficient social safety may be a primary cause of stigma-related health disparities in gender-and sexually-diverse populations [17].…”
Section: Introductionmentioning
confidence: 99%
“…While mental health concerns impact all members of society, studies have shown that mental health issues tend to affect members of sexual and gender minority communities at a greater level (Bränström et al, 2022;Jenkins et al, 2022;Kerr et al, 2022;Pease et al, 2022;N. S. Perry & Nelson, 2022;Pharr et al, 2019;Tabler et al, 2019;Tuthill et al, 2017).…”
Section: Mental Health Needs and Stigmatized Populationsmentioning
confidence: 99%